Unusual Accretion Disk in Algol - Type Binaries - KU Cyg - Szymanski, T.; Zola, S.; Siwak, M.; Ogloza, W. (Одеські астрономічні публікації, 2010)
We present new results obtained from analysis of Hα double peaked emission line observed at several phases. We confirm the results that KU Cyg harbours an eccentric shape, precessing accretion disk. The system mass ratio q=0.13 may indicat